2020
DOI: 10.2147/cmar.s227315
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anti-Proliferative and Apoptosis-Promoting Effect of microRNA-125b on Pancreatic Cancer by Targeting NEDD9 via PI3K/AKT Signaling</p>

Abstract: The expression of microRNA-125b (miR-125b) is low in a variety of cancers, including gastric, lung, bladder, thyroid, and esophageal cancers. However, its specific mechanism in pancreatic ductal adenocarcinoma (PDAC) remains unclear. This study is aimed to explore the role of miR-125b in PDAC. Methods: PDAC tissues and adjacent tissues were collected for miR-125b analysis by qRT-PCR. Different PDAC cell lines were cultured for miR-125b detection by qRT-PCR, and CAPAN1 cells were selected for the downstream exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Therefore, controlling the metastasis is important for the treatment of BC [ 32 , 33 ]. Various studies have shown that NEDD9 is highly expressed in malignant tumour tissues, such as glioma, colorectal and liver cancer tissues, and it has been suggested that it plays an important role in tumour invasion, metastasis and migration [ 34 , 35 ]. NEDD9 is a molecule related to tumour invasion and metastasis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, controlling the metastasis is important for the treatment of BC [ 32 , 33 ]. Various studies have shown that NEDD9 is highly expressed in malignant tumour tissues, such as glioma, colorectal and liver cancer tissues, and it has been suggested that it plays an important role in tumour invasion, metastasis and migration [ 34 , 35 ]. NEDD9 is a molecule related to tumour invasion and metastasis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that NEDD9 is highly expressed in malignant tumour tissues, such as glioma, colorectal and liver cancer tissues, and it has been suggested that it plays an important role in tumour invasion, metastasis and migration [ 34 , 35 ]. NEDD9 is a molecule related to tumour invasion and metastasis [ 34 , 35 ]. There have been several reports about the involvement of NEDD9 in the development of BC [ 36 , 37 ], but the precise molecular mechanism of NEDD9 in BC metastasis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (21) showed that upregulation of glutathione Stransferase mu-3 significantly inhibited cell proliferation by delaying the G0/G1 phase transition. Xue et al (22) observed that miR-125b could be downregulated in pancreatic ductal adenocarcinoma. On the contrary, upregulation of miR-125b could arrest the cells in the G0/G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 41 , 42 , 43 , 44 Additionally, NEDD9 expression negatively associated with miR ‐ 125a / b was shown in pancreatic cancer, lung adenocarcinoma and melanoma. 45 , 46 , 47 In pancreatic cancer and hepatocellular carcinoma, NEDD9 was reported to be regulated by miR ‐ 18a playing a key role during carcinogenesis. 48 , 49 In our study, we for the first time found that NEDD9 expression was negatively associated with miR ‐ 381 in AML.…”
Section: Discussionmentioning
confidence: 99%